1974
DOI: 10.1159/000152689
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Blood, Serum Protein and Enzyme Groups among the Fuyuge Speakers of the Goilala Sub-District

Abstract: A series of blood samples for Fuyuge speakers in Papua New Guinea have been tested for genetic variation in haemoglobin and in 8 blood groups, 5 serum protein and 15 enzyme systems, the latter being controlled by genes at 20 loci. Polymorphic variation was present for the ABO, MNS, Rh, P, and Lewis blood group systems, for the Hp and Tf serum protein systems and for the acid phosphatase, 6-PGD, ADA, PGM and PGM2 loci controlling red cell enzymes. In addition, a small number of variants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1975
1975
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…Adenylate Kinase Little AK testing has been reported from New Guinea, and so far no variation has been found [Malcolm et al, 1972;Woodfield et al, 1974], In the present surveys, 1 AK 2-1 subject was found among 49 Agarabe tested. Otherwise all were AK 1-1.…”
Section: Malate Dehydrogenasecontrasting
confidence: 45%
“…Adenylate Kinase Little AK testing has been reported from New Guinea, and so far no variation has been found [Malcolm et al, 1972;Woodfield et al, 1974], In the present surveys, 1 AK 2-1 subject was found among 49 Agarabe tested. Otherwise all were AK 1-1.…”
Section: Malate Dehydrogenasecontrasting
confidence: 45%
“…, with f(Pa) in the range 0.25-0.40 and Pc rare or absent; f(PGM:) high (>9); f(ADA2) comparatively high ( > 0.08); MDH3 present at low frequency; and PGM,' and ESDZ variants both present at polymorphic frequencies (Simmons and Booth, 1971;Omoto and Blake, 1972;Howells, 1973;Kirk et al, 1973;Woodfield et al, 1974;Blake and Omoto, 1975;Blake, 1976Blake, , 1978. Although the frequency of the TfDl allele is lower among the Gainj than among most other highland peoples, its frequency is known to vary widely throughout the region (Kirk et al, 1973;Serjeantson et al, 1973;Hazlett et al, 1979).…”
Section: Genetic Resultsmentioning
confidence: 99%
“…Serum samples were collected as a part of a blood group phenotype survey in PNG over 30 years ago [13,14]. Samples were from three geographically isolated areas of PNG: Tufi, Iruna and Fly River.…”
Section: Methodsmentioning
confidence: 99%